Reversible opening of the blood-brain barrier by claudin-5-binding variants of Clostridium perfringens enterotoxin's claudin-binding domain - Neuhaus, Winfried; Mahringer, Anne (Biomaterials, 2018)
The blood-brain barrier (BBB) prevents entry of neurotoxic substances but also that of drugs into the brain. Here, the paracellular barrier is formed by tight junctions (TJs) with claudin-5 (Cldn5) being the main sealing constituent. Transient BBB opening by targeting Cldn5 could improve paracellular drug delivery. The non-toxic C-terminal domain of Clostridium perfringens enterotoxin (cCPE) binds to a subset of claudins, e.g., Cldn3, -4. Structure-based mutagenesis was used to generate Cldn5-binding variants (cCPE-Y306W/S313H and cCPE-N218Q/Y306W/S313H). These cCPE-variants were tested for transient TJ opening using multiple in vitro BBB models: Primary porcine brain endothelial cells, coculture of primary rat brain endothelial cells with astrocytes and mouse cerebEND cells. cCPE-Y306W/S313H and cCPE-N218Q/Y306W/S313H but neither cCPE-wt nor cCPE-Y306A/L315A (not binding to claudins) decreased transendothelial electrical resistance in a concentration-dependent and reversible manner. Furthermore, permeability of carboxyfluorescein (with size of CNS drugs) was increased. cCPE-Y306W/S313H but neither cCPE-wt nor cCPE-Y306A/L315A bound to Cldn5-expressing brain endothelial cells. However, freeze-fracture EM showed that cCPE-Y306W/S313H did not cause drastic TJ breakdown. In sum, Cldn5-binding cCPE-variants enabled mild and transient opening of brain endothelial TJs. Using reliable in vitro BBB models, the results demonstrate that cCPE-based biologics designed to bind Cldn5 improve paracellular drug delivery across the BBB.